The Intellectual Evolution of Digital Literacy Studies: A Bibliometric Analysis of Scopus Publications - Loso Judijanto (The Eastasouth Journal of Information System and Computer Science, 2026)
This study aims to map and analyze the global research landscape of digital literacy through a bibliometric approach. Data were retrieved from the Scopus database and analyzed using VOSviewer software to examine co-authorship patterns, institutional collaborations, country contributions, keyword co-occurrence structures, and citation impact. The co-authorship analysis reveals that author-level collaboration in digital literacy research is not organized into a single integrated community but into four largely disconnected teams that are unified almost entirely through the boundary-spanning position of one prolific author, while institutional collaboration remains sparse and structured as a thin, crossing chain linking business and communication, management, and nursing faculties. At the country level, China and the United States function as dual central hubs, with Indonesia forming a substantial secondary hub that reflects the strong presence of Southeast Asian scholarship, alongside more selective participation from countries such as Canada, Australia, Spain, and the Russian Federation. As shown by the keyword co-occurrence analysis, the field is organized around four interconnected clusters covering the library- and bibliometric-oriented dimension of digital literacy, the artificial-intelligence-driven pedagogical dimension, the human-subject and disability-oriented dimension, and a smaller pandemic-related bridging dimension, with digital literacy, artificial intelligence, and human forming the dominant conceptual anchors. The overlay and density analyses further indicate a clear temporal shift from foundational information-literacy and human-subject themes toward generative-AI-oriented and bibliometric-mapping themes in more recent years. The citation analysis demonstrates that the field draws on cross-disciplinary foundational works spanning financial literacy, disability inclusion, multimodal literacy, and generative artificial intelligence. Taken together, these findings suggest that digital literacy research has developed into a globally distributed yet structurally fragmented field that is rapidly reorienting itself around the integration of artificial intelligence into literacy theory and practice.